Euro-Latin-American Cooperation Against Corruption and its Impact on Human Rights - Garciandia, Rosana (Araucaria, 2024)
Under the UN Convention against Corruption (UNCAC), as well as under regional conventions, Latin-American and European States are strengthening their efforts to combat corruption by, among other measures, consolidating their international cooperation. Building on the increasingly acknowledged impact of corruption on human rights, this paper explores how the substantive link between corruption and human rights could be unfolded to develop cooperation strategies against corruption with a positive impact on human rights. It does it using as examples a selection of initiatives of inter-regional cooperation against corruption between Europe and Latin-America.